Does progesterone differ in its effect on single and multiple pregnancy myometrium?. (16th November 2010) - Ballard, CK; Arrowsmith, S; Turton, P; Bricker, L; Neilson, J; Wray, S
Abstract : Twins in utero and their mothers are at a variety of risks; for example pre-eclampsia and prematurity. Large scale studies and reviews have confirmed a tocolytic benefit of progesterone in singleton pregnancies. In multiples however, similar studies have shown no benefit of progesterone. The reason for this difference is unknown. The authors considered it important therefore to investigate, under controlled in vitro conditions, how myometrium from singleton and multiple pregnancies responds to different doses of progesterone. Methods: Myometrial strips were prepared from biopsies obtained with informed consent from seven women with multiple pregnancy and six singletons undergoing Caesarean section at term. Strips were attached to a force transducer, superfused with physiological saline, and once stable contractions arose, cumulative doses of hydroxyl-progesterone from 1 to 100 μM were applied. Results: Contraction frequency was greater in the multiple pregnancies than singletons, but their amplitudes were comparable. A striking difference between multiples and singletons was found in the progesterone dose-response curves, with significant resistance to progesterone's effects being found in the former; at 10 μM progesterone, compared to control amplitude (100%), multiples produced significantly more force than singletons (62%±4% and 30%±14%, respectively, p=0.0048). Conclusion: These preliminary results suggest significant differences in both the inherent contractile properties in multiple pregnancies and in myometrial response to progesterone. The reduced efficacy of progesterone may be due to accelerated switching in progesterone isoforms in preparation for labour in multiple pregnancies, and is consistent with clinical findings, but leaves open the question of whether higher progesterone doses would be efficacious.